Differential regulation of intracellular factors mediating cell cycle, DNA repair and inflammation following exposure to silver nanoparticles in human cells - AshaRani, PV (BioMed Central, 2012)
BACKGROUND: Investigating the cellular and molecular signatures in eukaryotic cells following exposure to nanoparticles will further our understanding on the mechanisms mediating nanoparticle induced effects. This study illustrates the molecular effects of silver nanoparticles (Ag-np) in normal human lung cells, IMR-90 and human brain cancer cells, U251 with emphasis on gene expression, induction of inflammatory mediators and the interaction of Ag-np with cytosolic proteins. RESULTS: We report that silver nanoparticles are capable of adsorbing cytosolic proteins on their surface that may influence the function of intracellular factors. Gene and protein expression profiles of Ag-np exposed cells revealed up regulation of many DNA damage response genes such as Gadd 45 in both the cell types and ATR in cancer cells. Moreover, down regulation of genes necessary for cell cycle progression (cyclin B and cyclin E) and DNA damage response/repair (XRCC1 and 3, FEN1, RAD51C, RPA1) was observed in both the cell lines. Double strand DNA damage was observed in a dose dependant manner as evidenced in γH2AX foci assay. There was a down regulation of p53 and PCNA in treated cells. Cancer cells in particular showed a concentration dependant increase in phosphorylated p53 accompanied by the cleavage of caspase 3 and PARP. Our results demonstrate the involvement of NFκB and MAP kinase pathway in response to Ag-np exposure. Up regulation of pro-inflammatory cytokines such as interleukins (IL-8, IL-6), macrophage colony stimulating factor, macrophage inflammatory protein in fibroblasts following Ag-np exposure were also observed. CONCLUSION: In summary, Ag-np can modulate gene expression and protein functions in IMR-90 cells and U251 cells, leading to defective DNA repair, proliferation arrest and inflammatory response. The observed changes could also be due to its capability to adsorb cytosolic proteins on its surface.